问题 解答题
计算下面各题.
15÷
5
4
÷
8
7
25-
12
5
÷
6
25
(
3
5
+
4
25
÷
2
5
1
3
(
3
5
-
2
15
)÷(
1
12
+
5
6
)
12
17
÷3×
4
5
[1-(
1
4
+
3
8
)]÷
1
4
答案

(1)15÷

5
4
÷
8
7

=15×

4
5
×
7
8

=10

1
2

(2)25-

12
5
÷
6
25

=25-

12
5
×
25
6

=25-10,

=15;

(3)(

3
5
+
4
25
÷
2
5
)×
1
3

=(

3
5
+
4
25
×
5
2
)×
1
3

=(

3
5
+
2
5
)×
1
3

=1×

1
3

=

1
3

(4)(

3
5
-
2
15
)÷(
1
12
+
5
6
),

=

7
15
÷
11
12

=

7
15
×
12
11

=

28
55

(5)

12
17
÷3×
4
5

=

12
17
×
1
3
×
4
5

=

16
85

(6)[1-(

1
4
+
3
8
)]÷
1
4

=[1-

5
8
]×4,

=

3
8
×4,

=

3
2

填空题
选择题